Validity and Reliability of the Design and Technology Instrument - Kim Huei, Owi; Che Rus, Ridzwan; Kamis, Arasinah (International Journal of Psychosocial Rehabilitation, 2019)
This study was conducted to generate empirical evidence on the validity and reliability of the items for new instrument in Design and Technology (D&T) subject. The measurement of RBT subject instruments that had been prepared consisted of 41 skill items is distributed to 100 teachers. Cluster random sampling and simple random sampling methods were utilized in selecting a total of 100 secondary school teachers all over Peninsular Malaysia who teach the subject of D&T. Two stages of processes were used to identify and validate constructs. The first stage involved the identification of constructs using exploratory factor analysis method and the second stage was construct validation stage using the Rasch measurement model. The purpose of the establishment of this instrument is to measure the four main constructs of this study, which is; (1) Designing skill; (2) Sketching skill; (3) Applying Technology skill; (4) Designing in marketing skill. At the end of the analysis, it is found that there is a total of 13 polytomous items that were discarded because they did not fulfil the inspection criteria specified in accordance to the Rasch Model. The final instrument recorded a total of 27 polytomous items subsequently that can only be used to measure the four constructs of the study. In conclusion, this study has established valid constructs for development of instruments for measuring design and technology subject.